Questvertising as a new format of interactive advertising - Dolinski, Dariusz; Grzyb, Tomasz (Frontiers in Communication, 2025)
Ad avoidance is one of the most persistent challenges in online advertising, with users increasingly employing ad-blocking software or developing habitual strategies to ignore marketing content. One promising solution is to shift from passive advertising formats to interactive ones, which actively engage users in the communication process. This article introduces questvertising, a novel interactive advertising format designed to reduce ad avoidance by offering users a brief, engaging task in exchange for access to desired content. In a typical questvertising scenario, instead of being asked to purchase access to gated content (such as an article or video), users are presented with a short branded message followed by a multiple-choice question based on that message. A correct answer grants immediate access to the content—at no cost—thus integrating the ad experience seamlessly into the user journey. We tested the effectiveness of questvertising in a field study promoting a new coffee brand, Colibri Café (N = 11,006). Participants were randomly assigned to one of four conditions: a standard display banner, a single questvertising exposure, two spaced questvertising exposures, or a no-ad control. Brand awareness and associations were measured 26–51 h later. Results showed that a single questvertising exposure nearly doubled brand recall compared to the banner condition (59.0% vs. 31.2%), while two exposures increased it to 68.3%. Questvertising also significantly enhanced brand associations with South American origin (57.8–68.2% vs. 36.4%) and positive affect, with up to 30.1% selecting Colibri Café as the most appealing brand, compared to only 3.9% in the banner group. Traditional display advertising showed no significant advantage over the control. These findings demonstrate the considerable potential of questvertising as a more engaging and effective format of interactive advertising, particularly in combating ad fatigue and enhancing brand outcomes.